Production of semi-inclusive doubly heavy baryons via top-quark decays - Niu, Juan-Juan; Guo, Lei; Ma, Hong-Hao [UNESP]; Wu, Xing-Gang; Zheng, Xu-Chang (Amer Physical Soc, 2018)
In the paper, we present a detailed discussion on the semi-inclusive production of doubly heavy baryons (Xi(bc) and Xi(bb)) through top-quark decay channel, t -> Xi(bQ ') + (Q ') over bar + W+, within the framework of nonrelativistic QCD. In our calculations, the contributions from the intermediate diquark states < bc > [S-3(1)]((3) over bar /6), < bc > [S-1(0)]((3) over bar /6,) < bb > [S-1(0)](6,) and < bb > [S-3(1)]((3) over bar) have been taken into consideration. Main uncertainties from the heavy quark mass (m(c), m(b) or m(t)), the renormalization scale mu(r), and the nonperturbative transition probability have been estimated. For a comparison, we also analyze the production of doubly heavy baryons under the approximate fragmentation function approach. Estimated at the LHC or a High Luminosity LHC with L = 10(34-36) cm(-2) s(-1), there will be about 2.25 x 10(4-6) events of Xi(bc) and 9.49 x 10(2-4) events of Xi(bb) produced in one operation year through top-quark decays.